BEGINNING CRITICAL THINKING SKILLS FOR V ELEMENTARY SCHOOL STUDENTS IN BANDUNG - Suryana, Sabila Idzni; Sopandi, Wahyu; Sobari, Teti; Banawi, Anasufi (Sekolah Pascasarjana UPI, 2022)
The purpose of the study was to describe the initial critical thinking skills of elementary school students in Bandung. Descriptive qualitative method was used in this research by involving 64 fifth grade students in learning science of air material from three elementary schools in Bandung, West Java. The data was collected using an instrument in the form of a description test that includes all critical thinking indicators assisted by google form. The data were analyzed by calculating the percentage value of the students' answers and categorizing them into very high, high, medium, low, and very low. The results showed that in general the students' initial critical thinking abilities were included in the low category. Very low category 27 people (42.19%); low 27 people (42.19%); while 9 people (14.06%); and the height of 1 person (1.56%). Based on critical thinking indicators, aspects of Advanced Clarification and Strategies and Tactics fall into the very low category with an average percentage value of 21.25% and 33.44%, Elementary Clarification aspects fall into the low category (46.34%), Basic Support aspects is in the medium category (58.77%), while the Inferring aspect is in the high category (79.17%). In general, the critical thinking aspect of students in several elementary schools in Bandung is still in the low category (47.88%). These results indicate the need to improve the critical thinking aspects of students through habituation of these aspects in learning and the need for information on the impact of their effects through a follow-up study.